Levi's Elevation to the Priesthood in Second Temple Writings - Kugel, James (Harvard theological review, 1993)
In ancient Israel, the tribe of Levi was deemed to have a special connection with the service of God. Numerous biblical texts speak of the Levites as the priestly tribe or attribute to them certain special functions connected with cultic worship. But why exactly had the Levites been selected for such honors, and how did their selection come about? Several biblical narratives appear to have been designed in order to answer this question. Thus, the selection of the Levites is at one point connected with their zealousness following the Golden Calf incident (Exod 32:25–29), while elsewhere God's choice of the Levites seems to follow as a natural consequence after the death of the Levite Aaron (see Deut 10:8) or, possibly, to be the result of Moses' words in his final blessing of this tribe before his death (Deut 33:8– 10).